Analisis Hasil Belajar, Gender dan Self Regulated Learning (SRL) Mahasiswa Menggunakan Algoritma K-Means Clustering - Muhammad Wahid Syaifuddin; Septiana Wijayanti; Nugroho Arif Sudibyo (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this research is to use a clustering algorithm on learning outcomes, gender, and SRL. In this study, the K-Means clustering method was used. In this study, the calculation process is assisted by Orange software. Determination of the number of clusters with Orange software based on the Silhouette Score. The results show that there are seven clusters with three variables, namely learning outcomes, gender, and self-regulated learning. From these clusters, it can be used for group formation and student mapping.